AROUSING STUDENTS' INTEREST IN ART THROUGH CREATIVE ACTIVITIES (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This article provides a comprehensive analysis of the pedagogical, psychological and methodological importance of creative activities in the effective organization of fine arts classes in secondary general education institutions. The role of creative activities in the formation of students' aesthetic perception, artistic taste, imagination and creative thinking is covered in a scientifically and theoretically grounded manner. The study explores the potential of interactive methods, game technologies, an integrative approach and digital tools in art education. The article presents extended scientific conclusions on the role of creative activities in arousing students' sustainable interest in art, enhancing motivation and developing creative activity.